Peripheral neuropathy in the phase 3 ASPEN study of Bruton tyrosine kinase inhibitors for Waldenström macroglobulinemia - Benjamin M. Heyman; Stephen S. Opat; Björn E. Wahlin; Meletios-Athanasios C. Dimopoulos; Jorge J. Castillo; Alessandra Tedeschi; Constantine S. Tam; Christian Buske; Roger G. Owen; Véronique Leblond; Judith Trotman; Gisoo Barnes; et al. (Blood Advances)
Abstract: Peripheral neuropathy (PN) is a significant cause of morbidity associated with Waldenström macroglobulinemia (WM). The phase 3 ASPEN study compared the efficacy and safety of zanubrutinib with ibrutinib in patients with WM. This ad hoc analysis examined treatment outcomes with zanubrutinib or ibrutinib on PN symptoms associated with WM in patients enrolled in ASPEN. Logistic regression was performed between PN symptom resolution and several predictors. Health-related quality of life (HRQOL) was assessed using the validated European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30. Forty-nine patients with PN symptoms were included (zanubrutinib treated, n = 27; ibrutinib treated, n = 22). Overall, 35 patients (71.4%) experienced resolution of PN symptoms, with a median time to resolution of 10.1 months (range, 1-46.8). In cohort 1 (MYD88 mutation), the median time to PN symptom resolution was 4.6 months (range, 1.1-46.8) with zanubrutinib and 14.1 months (range, 1-44) with ibrutinib. Logistic regression demonstrated a significant relationship between PN symptom resolution and both major response and lower baseline anti–myelin-associated glycoprotein antibody levels. Patients with PN symptom resolution had greater improvement in HRQOL. Physical functioning improved in patients with PN symptom resolution and was unchanged in patients without resolution. Improvements observed in PN symptoms may be in response to a reduction in immunoglobulin M. Although further investigation is required, this analysis supports the potential use and further exploration of Bruton tyrosine kinase inhibitors to treat PN symptoms in patients with WM. This trial was registered at www.clinicaltrials.gov as #NCT03053440.